Prevalence and causes of blindness and visual impairment; and cataract surgical services in Katsina state of Nigeria. Issue 6 (5th September 2019) - Taryam, Manal Omran; Rabiu, Muhammad M; Muhammad, Nasiru; Oladigbolu, Kehinde; Abdurrahman, Halima
Abstract : Aim: To generate data on blindness and visual impairment for planning and monitoring a comprehensive eye care programme in Katsina state of Nigeria. Method: A rapid assessment of avoidable blindness (RAAB) survey methodology was used to select 3120 persons aged 50 years and over. The sample was selected using a multistage cluster randomised sampling. Each participant had visual acuity and lens assessment. Persons with vision less than 6/12 in any eye were assessed for the cause of visual impairment. Persons with cataract were asked why they had not had surgery. Data were captured electronically with the mRAAB Android-based software and analysed with STATA V.14 software. Results: A response rate of 90.1% was achieved. The age-sex adjusted blindness prevalence was 5.3% (95% CI 5.2% to 5.3%). Women were 30% more likely to be blind (OR 1.3, 95% CI 1.2 to 1.3). The principal causes of blindness were cataract (70%), other posterior segment (12%) and glaucoma (7%); 86.7% of blindness was avoidable. The prevalence of cataract blindness is 2.6% (95% CI 2.5% to 2.6%) with higher odds in women (OR 1.2, 95% CI 1.2 to 1.3, p<0.005). The cataract surgical coverage <6/60 for persons was 28.2% and women were 45% less likely to have had cataract surgery (OR 0.55, 95% CI 0.34 to 0.78, p<0.005). The major barriers to cataract surgery are lack of felt need and the cost of services. Conclusion: Katsina state of Nigeria has high burden of avoidable blindness affecting more women. The state eye care programme should have cataract services that are more accessible, affordable and gender sensitive.